Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1017/s0033291709991905
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of suicidality across the life span: The Isle of Wight study

Abstract: Factors of importance for long-term suicidality risk are evident in adolescence. These include family and experiential adversities as well as psychopathology. In particular, markers of adolescent worry and irritability appeared both potent risks and ones with additional effects beyond associations with adult disorder and adult neuroticism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
133
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(151 citation statements)
references
References 59 publications
12
133
1
Order By: Relevance
“…Brezo, Paris, & Turecki, 2006 for a review) and death by suicide (Duberstein, Conwell, & Cianne, 1994), even after controlling for the presence of established demographic and clinical risk factors (Farmer, Redman, & Harris, 2001;Yen, Shea, & Pagano, 2009). Neuroticism is also positively associated with suicide attempts in adults (Beautrais, Joyce, & Mulder, 1999;Nordstrom, Schalling, & Asberg, 1995;Pickles, Aglan, Collishaw et al, 2010). Also, the relationship between suicide attempts and neuroticism may be particularly pronounced for individuals endorsing strong intent (Statham, Heath, & Madden, 1998 In contrast to neuroticism, extraversion is inversely related to various aspects of suicidality (e.g., Lolas, Gomez, & Suarez, 1991;Pospiszyl, 1985).…”
Section: Personality and Suicidementioning
confidence: 99%
“…Brezo, Paris, & Turecki, 2006 for a review) and death by suicide (Duberstein, Conwell, & Cianne, 1994), even after controlling for the presence of established demographic and clinical risk factors (Farmer, Redman, & Harris, 2001;Yen, Shea, & Pagano, 2009). Neuroticism is also positively associated with suicide attempts in adults (Beautrais, Joyce, & Mulder, 1999;Nordstrom, Schalling, & Asberg, 1995;Pickles, Aglan, Collishaw et al, 2010). Also, the relationship between suicide attempts and neuroticism may be particularly pronounced for individuals endorsing strong intent (Statham, Heath, & Madden, 1998 In contrast to neuroticism, extraversion is inversely related to various aspects of suicidality (e.g., Lolas, Gomez, & Suarez, 1991;Pospiszyl, 1985).…”
Section: Personality and Suicidementioning
confidence: 99%
“…These results and the fact that adolescent irritability is an independent predictor of suicidality even at 30-year follow up 16 in the Isle of Wight study have made clear its significance for clinicians and researchers alike. However, several questions remain unresolved.…”
Section: Irritabilitymentioning
confidence: 84%
“…However, the current study considered prevalence of all cancers overall, in childhood and adulthood, in a cross-sectional study with a population-based sample while Brown et al (2010) looked at incident lung cancer using a prospective study design [15]. Evidence suggests that ACEs have been associated with risky sexual behaviors, [17][18][19] sexually transmitted infections, [7,8,19] chronic diseases such as cancer, [15,16] obesity, [42] depression [7,8,12,13], and smoking [42,43]. Research has also shown that ACEs are associated with risk factors for chronic disease [15] such as chronic obstructive pulmonary disease [44], liver disease [4], and ischemic heart disease [14].…”
Section: Discussionmentioning
confidence: 99%
“…ACEs have been linked to substance abuse [7][8][9][10][11], depression [7,8,12,13], cardiovascular disease [7,14], diabetes [7], cancer [7,15,16], risky sexual behaviors [17][18][19], sexually transmitted infections [7,8,19] suicidality [7,8,13,17,18], and premature mortality in adulthood [17]. Researchers have suggested examining multiple ACEs allowing for a potential assessment of a graded relationship between these exposures and health outcomes [6].…”
Section: Introductionmentioning
confidence: 99%